PTU-060 Enteral or parenteral feeding in intestinal graft dysfunction: any clues from serum citrulline?. (28th May 2012) - O'Connor, M; Vaidya, A; Smith, L; Friend, P
Abstract : Introduction: Citrulline has been successfully used as a marker for intestinal graft dysfunction after intestinal transplantation. 1 We have extended its use to direct enteral vs parenteral feeding in the early post operative period as well as during graft dysfunction presenting as high volume stoma effluent. Methods: Weekly serum citrulline concentrations were used in directing nutrition in all recipients of intestinal grafts. A cut off of 13 μmol/l was used. Patients with citrulline levels <13 mmol/l in the post operative period were kept on low volume enteral feed and maintained on TPN. Once the levels were above 13 mmol/l, enteral feeds were advanced to meet target rate and TPN independence was achieved. A similar pattern was followed with patients presenting with high output stomal effluent. These citrulline levels were then matched with histopathological diagnosis. Results: From October 2008, nine patients underwent a small bowel transplant at the Oxford transplant centre. Mean citrulline levels week one after transplantation were 15 mmol/l (range 12–17). Endoscopic biopsies in the first week showed signs of ischaemia reperfusion with significant oedema in the submucosa of the transplanted ileum. All these patients were maintained on TPN and had enteral feed (Peptisorb) at 30 ml/h. As mean citrulline levels increased patients progressed to full feed and TPN discontinued. Four patients presented with intestinal dysfunction after discharge from the hospital. These were all commenced on TPN if the citrulline level fell below 13 mmol/l. The first, had a citrulline of 19 mmol/l on presentation and. Biopsy demonstrated acute rejection. The second, presented with a high stoma output with a citrulline level of 9 mmol/l. Biopsy results revealed increase in mitotic figures as well as apoptosis and loss of tips of villi architecture. The third patient presented with a high stomal output and a citrulline of 18 mmol/l. Citrulline fell further to 9 mmol/l. The fourth patient presented with a high output and citrulline level of 13 mmol/l, dropping further to 6 mmol/l. His biopsy revealed dense mitotic activity in the face of increased apoptosis. He recovered in a span of 30 days with subsequent citrulline showing a rise. He was then weaned off TPN and commenced on diet. Mean time to graft dysfunction from transplantation was 240 days (range 46–450). Conclusion: Firstly serum citrulline is a good marker to direct nutritional therapy in the early post transplant period as well as during graft dysfunction. Competing interests: None declared. Reference: 1. Crenn P, et al. Postabsorptive plasma citrulline concentration is a marker of absorptive enterocyte mass and intestinal failure in humans. Gastroenterology 2000;119 :1496.